2018
DOI: 10.1039/c8ra03032d
|View full text |Cite
|
Sign up to set email alerts
|

N2O emission and bacterial community dynamics during realization of the partial nitrification process

Abstract: In this study, greenhouse gas emissions and microbial community succession during the realization of the partial nitrification (PN) process were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The next-generation sequencing was applied to determine the microbial community structure based on the universal primer pair of 16S rDNA 28 . The V4 amplicons were sequenced using primers 515F (GTGCCAGCMGCCGCGGTA) and 806R (GGACTACNVGGGTWTCTAAT) and the pair-ended method on the Illumina Miseq sequencing platform at Personal Biotechnology Co., Ltd. 29 .…”
Section: Methodsmentioning
confidence: 99%
“…The next-generation sequencing was applied to determine the microbial community structure based on the universal primer pair of 16S rDNA 28 . The V4 amplicons were sequenced using primers 515F (GTGCCAGCMGCCGCGGTA) and 806R (GGACTACNVGGGTWTCTAAT) and the pair-ended method on the Illumina Miseq sequencing platform at Personal Biotechnology Co., Ltd. 29 .…”
Section: Methodsmentioning
confidence: 99%
“…The next-generation sequencing was applied to determine the microbial community structure based on the universal primer pair of 16S rDNA (Liu et al, 2018). The V4 amplicons were sequenced using primers 515F (GTGCCAGCMGCCGCGGTA) and 806R (GGACTACNVGGGTWTCTAAT) and the pair-ended method by Illumina Miseq sequencing platform (Lv et al, 2016).…”
Section: High-throughput 16s Rdna Sequencingmentioning
confidence: 99%
“…It is known that the key to achieving stable partial nitrication is to sustainably retain AOB while eliminating NOB in the mainstream BNR process. 30,31 However, raw sewage that contains a few nitriers, especially the more efficient NOB in seeding as shown in Table 3, continuously inoculates the bioreactor, which might have a devastating effect on achieving stable partial nitrication. Duan et al reported that the continuously seeding of NOB in raw sewage resulted in different extents of ineffective NOB suppression in the mainstream activated sludge systems.…”
Section: The Intractable Challenge For Achieving Partial Nitrication In the Mainstreammentioning
confidence: 99%